First mapping of the main high conservation value forests (HCVFs) at national scale: The case of Italy. (3rd March 2016) - Maesano, M.; Lasserre, B.; Masiero, M.; Tonti, D.; Marchetti, M.
Abstract: Forest certification is one of the many tools that have been developed to achieve sustainable forest management. The Forest Stewardship Council (FSC) was the first organization to develop an independent forest certification scheme in early 1990s. FSC standards introduced the concept of high conservation value forests (HCVFs) that identifies forest areas with high conservation values (HCVs) according to six different categories including environmental services, social and cultural values, rare, threatened or endangered species, and ecosystems and habitats. HCVFs are becoming more relevant even beyond forest certification purposes, and the concept is increasingly being adopted and used as a tool for improving forest management operations. This paper represents a preliminary study for the identification and mapping of the main HCVFs in Italy. It is based on existing information and available datasets and identifies some out of six existing HCVs categories. The extent of forest areas identified as HCVFs in Italy varies according to the HCV category taken into consideration. Altogether, the HCVs investigated correspond to about 66% of the Italian forest. This preliminary study on HCVFs in Italy and GIS tools had proved to be a useful support for the identification and analysis of investigated areas for the purposes of both facilitating certification processes and improved management of national forests.